Rheological properties of hyaluronic acid-based fillers for facial cosmetic aesthetics (Research, Society and Development, 2023)
Hyaluronic acid-based dermal fillers are the most used materials in cosmiatry, and their clinical implications are linked to their viscoelastic properties. This study aimed to determine the rheological behavior of HA products used in Brazil by changing specific physicochemical characteristics under different test frequencies. Laboratory analyses of 0.9 mL of samples were performed in a TA-Instruments AR-1500ex Rheometer at 25 °C, at oscillation frequencies of 100, 10, 1, and 0.1 radians/second, considering the measurements of G′, G′′, and Tan δ. The value of G' increased as the oscillation frequencies were increased. In parallel, the changes in G" were the ones that varied the most for frequencies 0.1 and 1 radian/second. The maximum G' was observed with Hialurox Ultra Lift® 26 mg/g (793.45; 554.06; 423.44 Pa, 100, 10 and 1 rad/s, respectively). While the lowest G' values were obtained with Rennova Ultra Deep® (43.01; 19.75; 10.75 and 10.42 Pa at 100, 10, 1, 0.1 rad/sec, respectively). The changes that occurred in the investigated properties indicated that hyaluronic acid-based fillers vary when subjected to different conditions of shear rate, which should be considered in their clinical indication for choosing the most appropriate material according to the region to be treated.